The rights of the debtor in the preventive settlement procedure in the Saudi bankruptcy law - Alhamami, Saleh Muhammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The Saudi bankruptcy law approved a set of rights for the debtor in each of its procedures, including the rights related to the preventive settlement procedure, and the aim of highlighting these rights is to contribute to preserving them, achieving justice, and avoiding harm to the side of the bankrupt debtor, especially since the organizers' interest in the bankruptcy law It is primarily concerned with the creditor's side, and how to obtain his rights from the debtor.In this research, the debtor’s rights contained in the provisions of the law relating to the preventive settlement procedure will be shed light and collected within this frameworkThe research relied on the inductive and analytical approach, whereby the provisions of the Saudi bankruptcy law were extrapolated, then the rights of the debtor were extracted from its folds, and these rights were analyzed.The rights in this procedure are summarized as following: the right to request the debtor to initiate the procedure, to inform him of the date of consideration of the request, to request the suspension of claims during the procedure, to not claim debts other than the status during the procedure period, to maintain his contractual obligations, and to obtain financing.The research came out with a set of important results that reveal the comprehensiveness of the provisions of the Saudi bankruptcy law, its concern for the rights of all parties, including the debtor, as well as the expansion of the scope of application of the provisions of specific and spatial bankruptcy procedures, and the likeThe research also included a set of recommendations in which I saw addressing some observations during the analysis of these rights, such as not allowing the debtor to manage his activity during the period from the opening of the procedure, until the creditors have completed voting on the plan, as well as granting the creditor the right to demand the opening of the preventive settlement procedure, And not limiting this right to the debtor only, and so on.
Keywords: rights; ordinary debtor; small debtor; natural person; legal person; preventive settlement; bankruptcy system